Increased expression of STIM1/Orai1 in platelets of stroke patients predictive of poor outcomes. (23rd May 2017) - Dong, M.; Zheng, N.; Ren, L. J.; Zhou, H.; Liu, J.
Abstract : Background and purpose: The platelet activation that is mediated by store‐operated Ca 2+ entry via stromal interaction molecule (STIM1) and Orai1 Ca 2+ influx channels has been shown to play a key role in ischaemic stroke (IS). This study aimed to evaluate the impact of platelet STIM1/Orai1 protein expression on outcomes of IS. Methods: A total of 160 patients with acute non‐cardioembolic IS, among whom 45 patients had small‐vessel diseases and 115 patients had large‐vessel diseases, were evaluated. Patients were divided into two groups according to their baseline platelet STIM1/Orai1 protein expression: high‐expression group (HG) ( n = 80) and low‐expression group (LG) ( n = 80). Univariate and multivariate regression models were used to assess the correlation between STIM1/Orai1 expression and clinical outcomes, which included stroke severity that was measured based on the National Institutes of Health Stroke Scale and Stroke Impact Scale (SIS) at baseline and during the 3‐month follow‐up. Results: There were no significant differences in age, sex and cardiovascular risk factors between patients in HG and LG. However, HG had very high levels of biomarkers such as glycosylated hemoglobin, C‐reactive protein, homocysteine and high mobility group box‐1 protein (all P < 0.05). Although the baseline stroke severity (National Institutes of Health Stroke Scale score) was not obviously higher in HG than in LG, patients showed a better recovery score (SIS score) in LG than in HG (90.75 ± 13.65 vs. 80.68 ± 7.09; P = 0.022). STIM1/Orai1 expression was an independent predictor of the 3‐month stroke recovery (hazard ratio, 4.543; 95% confidence interval, 1.941–29.145; P = 0.029). Conclusions: A high expression level of platelet Orai1/STIMI1 was associated with poor clinical outcome (mortality and recurrence) and functional recovery (SIS scores) during the 3‐month follow‐up. Thus, we propose that these proteins are strongly predictive of life quality in patients with IS.